The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adma.202101312
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Materials for Selective Ion Separations at the Water–Energy Nexus

Abstract: Synthetic polymer membranes are enabling components in key technologies at the water–energy nexus, including desalination and energy conversion, because of their high water/salt selectivity or ionic conductivity. However, many applications at the water–energy nexus require ion selectivity, or separation of specific ionic species from other similar species. Here, the ion selectivity of conventional polymeric membrane materials is assessed and recent progress in enhancing selective transport via tailored free vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 153 publications
0
79
0
Order By: Relevance
“…The mechanisms underlying the delicate selectivity observed between similarly sized and charged monovalent ions have been increasingly studied in recent years. , Understanding the molecular details of these mechanisms is the key to design membranes for precise separations that can extend the use of polymeric membranes to applications beyond water desalination and purification. , While numerous experimental studies focused on explaining monovalent–monovalent ion selectivity by testing the permeation of monovalent anions, ,,, in the current study, we explored the transport and selectivity of monovalent cations, which demonstrate some intriguing transport phenomena, as we discuss below. More specifically, we measured the intrinsic permeability of four monovalent cations (i.e., lithium, sodium, potassium, and cesium; as chloride salts) at different pH and temperature values to extract their TST parameters using the methods described above (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms underlying the delicate selectivity observed between similarly sized and charged monovalent ions have been increasingly studied in recent years. , Understanding the molecular details of these mechanisms is the key to design membranes for precise separations that can extend the use of polymeric membranes to applications beyond water desalination and purification. , While numerous experimental studies focused on explaining monovalent–monovalent ion selectivity by testing the permeation of monovalent anions, ,,, in the current study, we explored the transport and selectivity of monovalent cations, which demonstrate some intriguing transport phenomena, as we discuss below. More specifically, we measured the intrinsic permeability of four monovalent cations (i.e., lithium, sodium, potassium, and cesium; as chloride salts) at different pH and temperature values to extract their TST parameters using the methods described above (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Filtration using polymer membranes is an essential technology for water purification and for supplying safe water at low cost and with low energy consumption [ 3 5 ]. Aromatic polyamide thin films have been used as the separation layer of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic polyamide thin films have been used as the separation layer of membranes. Recently, advanced water filtration membranes [ 5 ] with materials such as liquid-crystalline (LC) polymers [ 6 14 ], carbon nanotubes [ 15 ], and block polymers [ 16 ] have been proposed. For example, we developed nanostructured membranes with three-dimensional (3D) nano ionic channels from an ionic bicontinuous cubic (Cub bi ) LC monomer with a taper-shaped mesogen [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extraordinarily, Membrane distillation is a developing membrane separation technology through which combined membrane technique with distillation process (Liu et al, 1998;Meindersma et al, 2006;Liao et al, 2021), which has been indicated that the membrane distillation possessed excellent advantages, e.g., high separation efficiency, simple operation conditions, mild requirements on the interaction between membrane, and raw feed liquid (Smolders and Franken, 1989;Rezaei et al, 2018). Therefore, it is widely applied to seawater desalination, ultra-pure water preparation, and separation of an azeotropic mixture the like (Gong et al, 2019;Karahan et al, 2020;DuChanois et al, 2021). However, refrigerating capacity required for the membrane distillation process is generally supplied by mechanical refrigeration, which causes a membrane distillation system to have a complex structure and higher power consumption.…”
Section: Introductionmentioning
confidence: 99%